Flat Detector Computed Tomography Angiography with Intravenous Contrast Application: Feasibility for Visualization of Cerebral Arterial Vasculature. Issue 3 (28th December 2012) - Saake, Marc; Breuer, Lorenz; Goelitz, Philipp; Ott, Sabine; Struffert, Tobias; Doerfler, Arnd
<x xml:space="preserve">Abstract</x> ABSTRACT BACKGROUND AND PURPOSE The aim of our study was to evaluate flat detector computed tomography angiography with peripheral intravenous contrast material application (FD‐CTA) for visualization of cerebral arteries in comparison with intravenous multidetector computed tomography angiography (CTA) and intraarterial digital subtraction angiography (DSA). METHODS The study was approved by the local institutional review board and informed consent was obtained by all participants. Ten patients underwent FD‐CTA, CTA, and DSA of the cerebral arterial vasculature for suspected cerebrovascular disease. The image data were evaluated by two readers in consensus for the visualization of cerebral arterial segments on a 5‐point scale (0 = vessel cannot be distinguished; 4 = excellent image quality). The Wilcoxon signed‐rank test was used for statistical analysis. Note that P < .05 was considered to indicate a significant difference. RESULTS The depiction of cerebral arterial segments with FD‐CTA was significantly superior compared to CTA in most vessel segments (P < .05 in 20 of 23 anatomic regions) and was without significant difference compared with DSA in large and medium intracranial vessels. CONCLUSIONS The results suggest that the cerebral arteries can be visualized by FD‐CTA in high resolution, in many vessel segments comparable to DSA.